2012
DOI: 10.1002/srin.201100216
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Fe‐Containing Phases and Recovery of Iron and Its Oxides by Magnetic Separation from BOF Slags

Abstract: Steel slag normally contains a large amount of iron and its oxides. Therefore, it is a potential renewable resource in case of inadequate iron ore supply. To recover the metals from steel slag, two types of BOF slags were remelted at 1873 K. The liquid slags were cooled using four types of cooling conditions, namely, water granulation, splashing, air cooling, and furnace cooling, to investigate the influence of cooling rate on mineral components, especially the enrichment behavior of Fe‐containing minerals. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…In general, the crystallization temperatures of precipitated phases became lower with increasing the cooling rate from 10 K/min to 800 K/min, which is to be expected. A similar trend was reported previously concerning the crystallization behavior of synthetic coal ash slag [33] and BOF slag [34] under different cooling rates. It can be understood that the increasing of cooling rates resulted in larger increase in slag viscosity as temperature was lowered before crystallization commenced enabling a higher degree of undercooling (a lower crystallization temperature).…”
Section: Crystallization Properties Of the Slags Under Continuous supporting
confidence: 89%
“…In general, the crystallization temperatures of precipitated phases became lower with increasing the cooling rate from 10 K/min to 800 K/min, which is to be expected. A similar trend was reported previously concerning the crystallization behavior of synthetic coal ash slag [33] and BOF slag [34] under different cooling rates. It can be understood that the increasing of cooling rates resulted in larger increase in slag viscosity as temperature was lowered before crystallization commenced enabling a higher degree of undercooling (a lower crystallization temperature).…”
Section: Crystallization Properties Of the Slags Under Continuous supporting
confidence: 89%
“…The rationale put here for the difference in the grade of coarse and fine particles also agrees with few research works conducted on studying the of grindability of steel slag. The work done by Wang et al [25] also found similar results when studying the cementitious property of steel slag powder based on their size. In this study, XRD studies were conducted with fine and coarse fractions of steel slag, and it was observed that coarse particles contained more of RO phase and wustite phase while the finer fractions contained more C3S and C2S.…”
Section: Methodssupporting
confidence: 54%
“…The reactivity with water increases with the application of rapid cooling . Moreover, the slow cooling of BOF slag, promoting the good distribution of crystals, results in a fraction with high iron and low phosphorus content . By controlling the additions under a rapid cooling condition, the extraction of metallic iron can be performed by the carbothermic reduction reaction, and the remaining slag can be used for construction applications .…”
Section: Introductionmentioning
confidence: 99%